More Similiarities Than Differences: An International Comparison of CVD Mortality and Risk Factors in Women - Gholizedah, L.; Davidson, Patricia (Taylor & Francis Group LLC, 2008)
In this article we describe global cardiovascular risk factor trendsin women, both physiological and behavioral, in order to improvethe understanding of cardiovascular health of women. Our aim inpresenting this information is to inform interventions and policies toimprove the cardiovascular health of women. Although differencesare apparent between developing and developed countries, arange of commonalities exist that allow a global approach toimproving women’s health. A multifaceted approach consideringphysiological, social, economic, and political determinants iscritical to improve the cardiovascular health outcomes of women.